Single crewing in English and Welsh policing: frequency and associations with violence towards and injuries in officers - Houdmont, Jonathan; Elliott-Davies, Mary; Donnelly, Joan (Taylor & Francis, 2018)
There is limited contemporary evidence concerning whether single crewing – the deployment of unaccompanied police officers – presents a risk to officer safety. This exploratory self-report study examined the frequency of single crewing in England and Wales and associations with violence-related variables. Officers represented by the Police Federation of England and Wales contributed survey data on four forms of violent victimisation and injuries requiring medical attention arising from workrelated violence experienced over the 12 months to February 2016. Respondents for whom crewing was applicable to their role indicated the frequency with which they had been single crewed during the same period. Pearson’s χ 2 tests were used to characterise socio- and occupational-demographic factors associated with single crewing, violence, and injuries. Associations between single crewing frequency and the target variables were assessed using adjusted binary logistic regression to generate odds ratios and 95% confidence intervals. Among the 11,397 respondents who indicated that crewing was applicable to their role, 53% were often and 21% always single crewed. Relative to those who were never single crewed, the odds of being subjected to verbal insults and verbal threats were significantly elevated in officers who were often or always single crewed. The odds of physical attacks and injuries requiring medical attention were significantly elevated in officers who were always single crewed. There was no association between single crewing frequency and physical attacks with a weapon. These initial cross-sectional findings suggest that tailored crewing options might represent a means by which to reduce violence towards police officers. Keywords: crewing, injury, police, violence.